Development Review of Highly Efficient Sequential Power Amplifier with Extended Back-Off Range for Broadband Application - Keyuan Yang; Rongxing Yang; Pan Zhang; Wei Shi; Chunyu Hu; Weimin Shi (Energies)
Similar to a Doherty power amplifier (DPA), a sequential power amplifier (SPA) is mainly composed of a main amplifier, an auxiliary amplifier and a combiner. However, SPA breaks the bandwidth limitation of the impedance inverter in the DPA, and also simplifies the design procedure. Since the main amplifier has no load modulation, it is easy for the SPA to realize broadband operation and improve the output back-off (OBO) power range. Therefore, SPA has great advantages and potential in expanding bandwidth, improving drain efficiency and expanding the back-off range of a power amplifier simultaneously. This paper describes the evolution and classification of the SPA. First, the basic theory of the SPA is reviewed. Then, some two-way SPAs using coupler and circulator as a power combiner are discussed. Thirdly, the latest popular sequential load modulated balanced amplifier is overviewed.